Influences Of Freely Suspended Polyelectrolyte On Aggregation Kinetics Of Magnetic Nanoparticles - Azmi, Muhamad Syakir (Universiti Sains Malaysia, 2021)
This study was carried out to find the influences of freely suspended polyelectrolyte on the aggregation kinetic of coated magnetic nanoparticles. The nanoparticles was first coated with a polymer which is poly(sodium-4-styrenesulfonate) (PSS) and poly(diallyldimethylammonium chloride) (PDDA). It is hypothesized that the interplay between the depletion and electrosteric bridging effects would play a dominance role on influencing the colloidal stability of the coated magnetic nanoparticles. Such effect of having freely suspended polyelectrolyte in the suspension was studied at different concentration using UV-vis-spectrophotometer and qualitatively through colour change of the suspension over time. Through this study, it was observed that the aggregation rate and settling velocity of the naked IONPs suspension calculated was the highest at the values of 0.006/min and 0.0372mm/min, respectively. While PSS-IONPs and PDDA-IONPs has considerably lower aggregation rate which was 0.0021/min and 0.0027/min, respectively. The presence of the same charged polyelectrolyte in the suspension of coated nanoparticles will cause higher aggregation rate which was observed highest for the suspension of 100 ppm PSS-IONPs in 100 ppm PSS solution and 100 ppm PDDA-IONPs in 150 ppm PDDA solution with the rate of 0.0031/min and 0.055/min, respectively. Apart from that, the increase of concentration of polyelectrolyte in the suspension causes the sedimentation rate of nanoparticle clusters to decrease and lowest sedimentation rate observed was for suspension of 100 ppm PSS-IONPs in 100 ppm PSS solution and 100 ppm PDDA-IONPs in 100 ppm PDDA solution with the settling velocity of 0.00495mm/min and 0.0057mm/min, respectively. From imaging study, at higher concentration of polyelectrolyte an observable cluster size appeared earlier while the sedimentation rate slower.